Angiographic Characteristics of Cerebral Perfusion and Hemodynamics of the Bridging Artery After Surgical Treatment of Unilateral Moyamoya Disease - Zhang, Kun; Ren, Wei; Sun, Yu-Xue; Wang, Xin-Jun; Li, Chao-Yue; Wang, Zi-Liang; Li, Tian-Xiao; Gao, Bu-Lang (Frontiers in Neuroscience, 2022)
Purpose: To investigate the characteristics of cerebral perfusion and hemodynamics of bypass grafting in the treatment of Moyamoya Disease (MMD) using the iFlow color-coded flow map in comparison with magnetic resonance imaging perfusion weighted imaging (MRI PWI) and computational fluid dynamic (CFD) analysis. Materials and methods: MMD Patients treated with bypass grafting who had undergone MRI PWI and digital subtraction angiography (DSA) for iFlow flow map was retrospectively enrolled. CFD was performed for calculating the hemodynamic stresses around the bypass grafting. Results: Forty-five patients with unilateral MMD treated with bypass surgery were enrolled. The bypass surgery was successful in all patients, with no severe neurological complciations during the periprocedrual period. Followed up for 4-12 months (median 5.5), the neurological function was good in all patietns. The cerebral blood flow (CBF), cerebral blood volume (CBV), mean transit time (MTT), and TTP were significantly (P<0.05) improved in the MCA distribution area on the operation side before and after vascular bypass, and the difference of TTP (s) measured from the proximal bifurcation of common carotid artery to the confluence of sinus was also significanl (P<0.05). A significant (P<0.05) positive correlation existed in the perfusion parameters between the iFlow blood perfusion and the MRI-PWI perfusion, with the r value for TTP of 0.765 (P<0.01). The iFlow color - coded blood flow map showed warm color changes on the diseased side, similar to those of on the contralateral side. In CFD analysis, the hymodynamic stresses were all improved in and around the bypass grafting and distal vessels, beneficial to blood flow entering distal arterial branches. Conclusion: iFlow color-coded flow map can be used to analyze cerebral perfusion after bypass grafting for MMD, similar to MRI PWI, and CFD can be used to analyze the hemodynamics after bypass grafting, revealing improved hemodyanmics to promote blood flow entering distal arteries.